2014
DOI: 10.1037/law0000025
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in couple relationship education (CRE): Overlooked evidence and implications for research and policy.

Abstract: Government interest in strengthening families in the United States and Great Britain has contributed to a rapid growth in couple relationship education (CRE) interventions, with a recent increase in programs for low-income families. We describe the policy contexts that initially led to increased support for CRE in both countries but now threaten its continuation. We summarize meta-analytic research and discussions of single studies by authors who draw opposing inferences about CRE effectiveness, often from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 99 publications
1
81
1
Order By: Relevance
“…Because RE mostly did not elicit statistically significant effects in fathers and father‐specific RE programs, future evaluation studies need to examine how men can be approached with regard to program content, workshop settings, and general teaching methods. Up to now, it can be concluded that working with both partners is the most effective approach (see Table ; Cowan & Cowan, ), and this might also hold for programs focusing on fatherhood.…”
Section: Discussionmentioning
confidence: 99%
“…Because RE mostly did not elicit statistically significant effects in fathers and father‐specific RE programs, future evaluation studies need to examine how men can be approached with regard to program content, workshop settings, and general teaching methods. Up to now, it can be concluded that working with both partners is the most effective approach (see Table ; Cowan & Cowan, ), and this might also hold for programs focusing on fatherhood.…”
Section: Discussionmentioning
confidence: 99%
“…Skepticism about CRE has been countered in a series of meta‐analyses and rejoinders by Hawkins and colleagues (Fawcett, Hawkins, Blanchard, & Carroll, ; Hawkins et al, ), showing that CRE programs, using many program models (with PREP as a leading systematically researched example; Stanley, Blumberg & Markman, ; Stanley et al, ) do in fact tend to produce improvements in couple communication. Our review of this issue (P. A. Cowan & Cowan, ) concluded that “from both research and policy perspectives, there are too many positive findings to give credence to the claim that CRE programs should be discontinued and funding directed elsewhere” (p. 361), while acknowledging that there are too many negative findings to assume automatically that every couples group program will be effective. Meta‐analyses, in effect, reported the average effect size of the CRE programs included in the analysis.…”
Section: A Personal and Professional Perspective On Preventive Intervmentioning
confidence: 99%
“…Variations in effectiveness were found between sites. A critique of these larger studies suggests that more can be learned from disaggregating sites and uncovering and learning more about site/program‐specific implementation designs and outcomes (Cowan & Cowan, ).…”
Section: Discussionmentioning
confidence: 99%